Asymmetric jurisdiction clauses under the Brussels-Lugano and Hague regimes - Monico, Rebekka (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Asymmetric jurisdiction clauses are choice of court agreements which bind one party to bring proceedings exclusively before the designated court and give the other party a right to choose, in addition to that court, other competent courts. The most common type of asymmetric clauses are the so-called Rothschild clauses. The article considers the enforceability requirements which asymmetric clauses must satisfy in order to be covered by the Brussels-Lugano regime, their effects under Regulation 1215/2012 and the Lugano Convention of 2007 and the issue of whether asymmetric clauses are covered by Art. 31(2) of Regulation 1215/2012, as well as the applicability of the Hague regime. To this end, reference is made to the relevant jurisprudence of the ECJ and national courts, with particular reference to the recent Lastre judgment in which the ECJ imposed for the first time limits on the validity of asymmetric clauses, while leaving open some important questions.
Keywords: Asymmetric jurisdiction clauses; Brussels-Lugano regime; enforceability requirements; effects; applicability of the Hague regime